2013
DOI: 10.1063/1.4812807
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén wave collisions, the fundamental building block of plasma turbulence. II. Numerical solution

Abstract: This paper presents the numerical verification of an asymptotic analytical solution for the nonlinear interaction between counterpropagating Alfvén waves, the fundamental building block of astrophysical plasma turbulence. The analytical solution, derived in the weak turbulence limit using the equations of incompressible MHD, is compared to a nonlinear gyrokinetic simulation of an Alfvén wave collision. The agreement between these methods signifies that the incompressible solution satisfactorily describes the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 19 publications
2
65
0
Order By: Relevance
“…Various explanations for why r A <1 have been advanced, including local in k ‐space dynamo action [ Pouquet et al , ; Grappin et al , ], small‐scale reconnection, with current sheets more intense than the nearby vorticity coherent structures [ Matthaeus and Lamkin , ], and a perturbation theory approach that indicates two counterpropagating Alfvén waves drive a k z =0 purely magnetic structure [ Howes and Nielson , ; Nielson et al , ]. For the case of solar wind fluctuations, Yokoi [] has shown that an approximately distance‐independent value of r A ≈1/2 emerges as a consequence of balance between the dominant terms in a (time steady) transport equation for the energy difference, E v − E b (equivalent to r A ).…”
Section: Resultsmentioning
confidence: 99%
“…Various explanations for why r A <1 have been advanced, including local in k ‐space dynamo action [ Pouquet et al , ; Grappin et al , ], small‐scale reconnection, with current sheets more intense than the nearby vorticity coherent structures [ Matthaeus and Lamkin , ], and a perturbation theory approach that indicates two counterpropagating Alfvén waves drive a k z =0 purely magnetic structure [ Howes and Nielson , ; Nielson et al , ]. For the case of solar wind fluctuations, Yokoi [] has shown that an approximately distance‐independent value of r A ≈1/2 emerges as a consequence of balance between the dominant terms in a (time steady) transport equation for the energy difference, E v − E b (equivalent to r A ).…”
Section: Resultsmentioning
confidence: 99%
“…In the Large Plasma Device (LAPD ) at UCLA, 9 experiments have been conducted to understand the nonlinear evolution of Alfvén wave collisions 115 -the nonlinear interactions among counterpropagating Alfvén waves, proposed as the fundamental mechanism mediating turbulent energy transfer to small scales in early studies of MHD turbulence. 116,117 Asymptotic analytical solutions for the evolution of Alfvén wave collisions in the weakly nonlinear limit 115 have been confirmed numerically with gyrokinetic numerical simulations in the MHD regime 118 and verified experimentally in the laboratory, 119-123 establishing Alfvén wave collisions as the fundamental building block of astrophysical plasma turbulence. The success of this experimental investigation of Alfvén wave collisions has laid the foundation for subsequent advances in our theoretical understanding of how current sheets arise self-consistently in plasma turbulence, 70,124 the role played by resonant wave-particle interactions in the dissipation of these current sheets, 72 and how collisions between localized Alfvén wavepackets in the strongly nonlinear limit mediate the turbulent cascade of energy to small scales.…”
Section: A Plasma Turbulencementioning
confidence: 85%
“…The amplitude of the initial wavepackets is parameterized by the nonlinearity parameter (Goldreich & Sridhar 1995), defined by taking the ratio of the magnitudes of the linear to the nonlinear terms in the incompressible MHD equations Nielson et al 2013). In terms of Elsasser variables, defined by z ± = u±δB/ 4π(n 0i m i + n 0e m e ), the nonlinearity parameter is defined by χ ± ≡ |z ∓ · ∇z ± |/|v A · ∇z ± |, where χ ± characterizes the strength of the nonlinear distortion of the z ± Alfvén wave by the counterpropagating z ∓ Alfvén wave.…”
Section: Simulationmentioning
confidence: 99%